Digital Innovation in East Asia : Do Restrictive Data Policies Matter? - Ferracane, Martina Francesca (World Bank, Washington, DC, 2020)
Digital technologies encourage companies to innovate with new processes, goods, and services, which ultimately enhance their competitiveness in local and global markets. This paper analyzes whether a wide set of data restrictions are negatively associated with digital innovation of firms. The paper develops an index of data restrictions that measures the level of data policy restrictiveness for 15 East Asian countries over time. Using various firm-level data sets, the analysis shows that data restrictions inhibit firms' ability to innovate. The analysis takes into account that data restrictions are likely to have a greater impact in sectors that are more reliant on software. Regressions show that in countries that have more restrictive data policies, firms are less likely to use foreign technologies through licensing as part of their innovation process. Country-specific cases for which data are available also show that restrictive data policies are negatively associated with firms' likelihood of using intangible assets, such as patents and goodwill, for performing innovation (in Malaysia and China) and developing innovations as a result of research and development that are new to the market (in Vietnam). The paper concludes that open data policies are likely to foster digital innovation.